THE EFFECT OF POLICY, AUDIT QUALITY, AUDITOR INDEPENDENCE, AND EFFECTIVENESS ON VILLAGE FUND MANAGEMENT TRANSPARENCY (Case Study On Village Government In Matangkuli District, North Aceh Regency) - Sri Arini; Juliana Ariska; Rico Nur Ilham; Ghazali Syamni; Nurlela (Universitas Efarina, 2023)
This study aims to determine how the influence of policies, audit quality, auditor independence, and effectiveness on the transparency of village fund management in Village Governments in Matangkuli District, North Aceh Regency. Policies in this study are measured by indicators consisting of planning, organizing, implementing, and supervising. Then audit quality variables are measured using indicators consisting of system quality, audits are carried out carefully, audits are carried out according to procedures, and skepticism. Furthermore, auditor independence is measured using indicators consisting of free from intervention, neutral, review from fellow auditors, and free from pressure. Meanwhile, effectiveness is measured using indicators consisting of clarity of goals to be achieved, clarity of strategies for achieving goals, a steady process of analysis and policy formulation, careful planning, and the preparation of appropriate programs. As well as the variable of transparency of village fund management is measured using indicators consisting of timely, clear, accurate, comparable, and easily accessible. The data used in this study is primary data obtained by distributing questionnaires to 225 respondents or communities in various villages in Matangkuli District, North Aceh Regency which were used as samples in this study. The data analysis technique used is multiple linear regression analysis using the help of SPSS software version 26. The results showed that policies, audit quality, auditor independence, and effectiveness had a positive and significant effect on the transparency of village fund management in Village Governments in Matangkuli District, North Aceh Regency.